Role of annealing temperature on electrical and optical properties of Al-doped ZnO thin films - Gurbuz, Osman; Guner, Sadik (ELSEVIER SCI LTD, 2015)
Undoped ZnO and Al-doped ZnO (AZO) thin films 200 nm thick were grown on polished and fused silica (SiO2) substrates by room temperature RF magnetron sputtering. High-purity ZnO (99.99%) and Al (99.999%) target materials were used. The samples were annealed at 300 degrees C, 400 degrees C, and 500 degrees C for 45 min in N-2 ambient gas. The effects of the annealing temperature on crystal structure, optical properties, and resistivity of the AZO thin films were systematically explored. As grown samples exhibit single crystalline Wiirtzite structure with preferred orientation along c axis from substrate surface. The crystal quality decreases with increasing amount of Al concentration. Annealing process increases the long range crystal order of films. Optical transmittance measurements show that all samples annealed at 500 degrees C have average 80% transparency in the visible light. Optical band gap values range between 3.23 eV to 3.72 eV for as grown and annealed samples. The electric conductivity of the AZO films increases with increasing Al concentration. The annealing process especially at 400 degrees C provides the best conductivity due to the improved crystal structure and carrier concentration of films. The minimum resistivity value of 9.40 x 10(-05) Omega cm was measured for the Al12.30ZnO film after annealing. The mobility decreases due to increase in grain boundary scattering. (C) 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Al-doped ZnO; RF Magnetron sputtering; Optical and electrical properties; SUBSTRATE-TEMPERATURE; ZINC-OXIDE; MAGNETOOPTICAL PROPERTIES; DEPOSITION; SUBSTITUTION; PARAMETERS; SURFACE; Materials Science